Slow extensional flow past a non-omogeneous porous spherical shell - Rajvanshi, Satish Chandra; Wasu, Sargam (Zielona Góra: Uniwersytet Zielonogórski)
An analytical investigation of extensional flow past a porous spherical shell of finite thickness with velocity slip at the surface is presented. The permeability of the shell varies continuously as a function of the radial distance. The flow in the porous region is assumed to obey Darcy`s Law. The drag has been calculated in terms of normal volume flux rate per unit area of the outer and inner surfaces. Particular cases of flow past a homogeneous sphere and no-slip boundary condition have been deduced.
Keywords: porous medium; Stokes flow; permeable shell; extensional field; velocity slip